Detention of Children by Public Prosecutors in General Criminal Cases: A Case Study of the Buton District Prosecutor’s Office - Budi Hermansyah; Hambali Thalib; Abdul Qahar (Al-Ishlah: Jurnal Ilmiah Hukum, 2025)
This study examines the practice of child detention by the Public Prosecutor in general criminal cases at the Buton District Prosecutor’s Office, focusing on its conformity with the principles of ultimum remedium and the best interests of the child as mandated by the Juvenile Criminal Justice System Law (UU SPPA). Although the legal framework emphasizes that detention should only be applied as a last resort, empirical findings indicate a tendency toward overuse: from 47 child cases handled between 2020 and 2025, 41 children were detained while only 6 were not. The majority of cases involved theft, violence, narcotics offences, and sexual crimes. Survey data show that 90% of respondents perceived detention as “effective,” reflecting a preference for legal certainty and public order rather than rehabilitation and restorative justice. The study identifies three key factors contributing to this pattern: limited understanding of restorative justice principles, structural constraints such as inadequate child-specific detention facilities and inconsistent inter-agency coordination, and cultural pressures from society and the media that encourage punitive approaches. The findings highlight a significant disparity between normative child protection standards and prosecutorial practices. Strengthening restorative justice, expanding non-custodial measures, improving infrastructure, and enhancing institutional coordination are crucial for aligning detention practices with child protection principles